2018
DOI: 10.1242/jeb.167825
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic benefits of prior anoxia exposure in buffering anoxia stress in a soil-pupating insect

Abstract: Oxygen is essential for most animals, and exposure to a complete lack of oxygen, i.e. anoxia, can result in irreparable damage to cells that can extend up to the organismal level to negatively affect performance. Although it is known that brief anoxia exposure may confer cross-tolerance to other stressors, few data exist on the biochemical and organismal consequences of repeated intermittent bouts of anoxia exposure. In nature, the Caribbean fruit fly, (Diptera: Tephritidae), is frequently exposed to heavy tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…can elicit experience-mediated resilience for a variety of taxa (i.e. fruit fly, coral, fish, zebra finch, mice) increasing CSR, fitness and compensatory/anticipatory responses under subsequent stress exposures (Brown et al, 2002;Costantini et al, 2012;Jonsson and Jonsson, 2014;Visser et al, 2018;Zhang et al, 2018). Further, early-life development presents a sensitive stage to elicit adaptive phenotypic adjustments (Fawcett and Frankenhuis, 2015), prompting investigation of environmental stress acclimation under a rapidly changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…can elicit experience-mediated resilience for a variety of taxa (i.e. fruit fly, coral, fish, zebra finch, mice) increasing CSR, fitness and compensatory/anticipatory responses under subsequent stress exposures (Brown et al, 2002;Costantini et al, 2012;Jonsson and Jonsson, 2014;Visser et al, 2018;Zhang et al, 2018). Further, early-life development presents a sensitive stage to elicit adaptive phenotypic adjustments (Fawcett and Frankenhuis, 2015), prompting investigation of environmental stress acclimation under a rapidly changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…This hormetic-like response (Calabrese et al , 2007; Costantini, 2014) demonstrates a benefit of early stress-priming for later performance and the adaptive plasticity of P. generosa to elevated p CO 2 . Use of hormesis to conceptualize carry over effects of mild stress exposure is largely confined to model insects, plants, and microorganisms (Lee et al , 1987; Calabrese and Blain, 2009; López-Martínez and Hahn, 2012; Visser et al , 2018). For example, Visser et al (Visser et al , 2018) found the Caribbean fruit fly, Anastrepha suspensa , exposed to oxidative stress early in life enhanced survivorship and investment in fertility and lipid synthesis under subsequent stress during adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Use of hormesis to conceptualize carry over effects of mild stress exposure is largely confined to model insects, plants, and microorganisms (Lee et al , 1987; Calabrese and Blain, 2009; López-Martínez and Hahn, 2012; Visser et al , 2018). For example, Visser et al (Visser et al , 2018) found the Caribbean fruit fly, Anastrepha suspensa , exposed to oxidative stress early in life enhanced survivorship and investment in fertility and lipid synthesis under subsequent stress during adulthood. Further mechanistic molecular and biochemical assessments under different stress intensities (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, starvation stress in larval honeybees leads to subsequent starvation tolerance as adults (Wang et al, 2016b;Wang et al, 2016a). In a similar manner, anoxia exposure during the development of the Caribbean fruit fly confers later anoxia resistance in adults (Visser et al, 2018). Early life mild heat stress in the zebra finch has also been shown to lower oxidative damage induced by heat stress in adult life (Costantini et al, 2012).…”
Section: Introductionmentioning
confidence: 97%